Effects of Glycerol and Diameter of Holes in Breaker Plate on Performance of Screw Mixer for Nanocomposites (Agricultural Engineering, 2017)
A breaker plate of a screw mixer is an efficient mixing device for use in homogenizing nanocomposites. This research was undertaken to investigate the effects of glycerol and diameter of holes in a breaker plate on performance of a screw mixer for nanocomposites. Samples of the nanocomposites were formulated by blending 1000 g cassava starch, 45-55% glycerol and 2% magnetite nanoparticles; and used to evaluate the performance of a locally developed screw mixer at 5 mm and 7 mm diameters of holes in its breaker plate. The effects of glycerol and diameter of holes in the breaker plate on mixing index, amount of unmixed nanocomposites and output/1000g were evaluated as performance indices for 1 hour. Empirical models were determined for predicting the performance of the mixer within the designed criteria. The results showed that the output/1000g and the mixing index increased with higher glycerol and diameter of holes in the breaker plate. However, the amount of unmixed nanocomposites decreases with a higher diameter of holes in the breaker plate (p < 0.05). The maximum output/1000g and mixing index lies between 5 mm diameter of holes in the breaker plate and 55% glycerol concentration with an approximate desirability of 0.60. The empirical models developed were fit (R2=0.89, p < 0.05); and there were no significant differences between actual and predicted values. The results suggest application of 5 mm diameter of holes in the breaker plate for homogenizing nanocomposites for optimum performance.